1975
DOI: 10.1017/s0033291700056646
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic antidepressants and tryptophan in unipolar depression

Abstract: SynopsisDepressed patients (unipolar) were given one of the following combinations in an attempt to test aspects of the ‘amine hypothesis’ and to find a preferential therapy: (1) clomipramine; (2) clomipramine and tryptophan; (3) desipramine and clomipramine, and (4) desipramine and tryptophan. Treatment (2) should have given optimal potentiation of 5-HT neurones and (3) and (4) should have acted similarly on both serotoninergic and adrenergic pathways. In no group was there any evidence of accelerated recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…L‐tryptophan augmentation was found to be effective in increasing the antidepressant response with phenezine sulphate, 71 clomipramine, 72,73 tranylcypromine, 74 and fluoxetine 75 . Earlier clinical studies using tricyclics showed no adjunctive benefit compared with placebo, 76,77 although many of those studies were of weak methodological design.…”
Section: Introductionmentioning
confidence: 99%
“…L‐tryptophan augmentation was found to be effective in increasing the antidepressant response with phenezine sulphate, 71 clomipramine, 72,73 tranylcypromine, 74 and fluoxetine 75 . Earlier clinical studies using tricyclics showed no adjunctive benefit compared with placebo, 76,77 although many of those studies were of weak methodological design.…”
Section: Introductionmentioning
confidence: 99%
“…Alino ef al. (1973) and Shaw et al (1975) found addition of T of no value, while Wdlinder et al (1976) demonstrated a more rapid improvement in patients who received both drugs. In a recent double-blind study by d' Elia et al (1977a) the combination of peroral T and ECT showed no advantage to ECT and placebo.…”
mentioning
confidence: 99%
“…As behavioural and neurological toxicity has been reported at tryptophan dosages of 2 g or more per day, tryptophan in this combination should be commenced at a dosage of 500 mg daily and slowly increased. Seven' double-blind studies of the tricyclictryptophan combination in non-resistant depressed samples have been undertaken (Lopez-Ibor Alino et al 1973;Roos 1976;Shaw et al 1975;Walinder et al 1976;Chouinard et al 1979;Walinder et al 1981;Thompson et al 1982). Four used the more serotonin-specific tricyclics, clomipramine (Roos 1976;Shaw et al 1975;Walinder et al 1976) and zimelidine (Walinder et ul.…”
Section: Combination Of Tricyclic Antidepressants and Monoamine Oxidamentioning
confidence: 99%